Challenges in Internet Addiction Disorder: Is a Diagnosis Feasible or Not? - Musetti, Alessandro; Cattivelli, Roberto; Giacobbi, Marco; Zuglian, Pablo; Ceccarini, Martina; Capelli, Francesca; Pietrabissa, Giada; Castelnuovo, Gianluca (Frontiers in Psychology, 2016)
An important international discussion began because of some pioneer studies carried out by Young (1996a) on the Internet Addiction Disorder. In the fifth and most recent version of the DSM there is no mention of this disorder and among researchers there are basically two opposite positions. Those who are in favor of a specific diagnosis and those who are claiming the importance of specific criteria characterizing this behavior and the precise role it has in the patient’s life. The aim of the present paper is to answer the question whether it is possible or not to formulate diagnoses of internet related disorders. We revised literature on the history of diagnostic criteria, on neurocognitive evidence, on the topic debate and on IAD instrumental measures. We found that the disorder was not univocally defined and that the construct was somehow too broad and generic to be explicative for a diagnosis. Indeed, the models are borrowed from other addiction pathologies and they are often formulated before the development of internet as intended in current society. In conclusion, we think we need a more innovative, integrated and comprehensive model for an IAD diagnosis.